The dog as a preclinical model to evaluate interface morphology and micro-motion in cemented total knee replacement - Mann, K. A.; Miller, M. A.; Khorasani, M.; Townsend, K. L.; Allen, M. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objectives: This study investigated cemented fixation of the tibial component from a canine total knee replacement preclinical model. The objective was to determine the local morphology at the material interfaces (implant, cement, bone) and the local relative micro-motion due to functional loading following in vivo service.Methods: Five skeletally mature research dogs underwent unilateral total knee replacement using a cemented implant system with a polyethylene (PE) monobloc tibial component. Use of the implanted limb was assessed by pressure-sensitive walkway analysis. At 60 weeks post-surgery, the animals were euthanatized and the tibia sectioned en bloc in the sagittal plane to create medial and lateral specimens. High resolution imaging was used to quantify the morphology under the tray and along the keel. Specimens were loaded to 50% body weight and micro-motions at the PE-cement and cement-bone interfaces were quantified.Results: There was significantly (p = 0.002) more cement-bone apposition and interdigitation along the central keel compared to the regions under the tray. Cavitary defects were associated with the perimeters of the implant (60 ± 25%). Interdigitation fraction was negatively correlated with cavitary defect fraction, cement crack fraction, and total micro-motion.Clinical significance: Achieving good inter-digitation of cement into subchondral bone beneath the tibial tray is associated with improved interface morphology and reduced micro-motion; features that could result in a reduced incidence of aseptic loosening. Multiple drill holes distributed over the cut tibial surface and adequate pressurization of the cement into the subchondral bone should improve fixation and reduce interface micro-motion and cavitary defects.
Keywords: Canine; knee joint replacement; implant fixation; aseptic loosening; micro-motion; cavitary defects